Modification strategy for controllable grafting ratio of multiple ligands on surfaces of inorganic nanoparticles

By designing a special structure initiator and polymer connection strategy, the problem of uncontrollable graft density in the surface multi-ligand modification of inorganic nanoparticles is solved, the precise control of graft ratio and simplification of the synthesis process is achieved, and the nanoparticles are improved Application performance.

CN119306966AActive Publication Date: 2025-01-14HUBEI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411504013.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-14
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

In the existing multi-ligand modification technology on the surface of inorganic nanoparticles, the graft density is uncontrollable, resulting in inaccurate functional expression. Especially when multi-ligand modification, the graft ratio varies greatly, affects performance, and the synthesis steps are complex and inflexible. .

Method used

Design an initiator with a special structure, containing initiating group A that can induce atom transfer radical polymerization and groups B and C that can react with each other. Group B first adopts a protective strategy to reduce the reaction activity, and synthesizes different types through ATRP polymerization. , polymers of different molecular weights, and covalent bonds are formed through chemical reactions to achieve the connection of different types of polymers, simplifying the steps and ensuring the controllability of the graft ratio.

Benefits of technology

The controllable modification of the graft ratio of multiple ligands on the surface of inorganic nanoparticles is realized, which simplifies the synthesis process, improves the stability and designability of polymer ligands, and is suitable for the surface modification of various inorganic nanoparticles, enhancing the Application performance of nanoparticles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005103285340000011
    Figure HDA0005103285340000011
  • Figure HDA0005103285340000012
    Figure HDA0005103285340000012
  • Figure HDA0005103285340000021
    Figure HDA0005103285340000021
Patent Text Reader

Abstract

The invention discloses a modification strategy for controlling the grafting ratio of multiple ligands on the surfaces of inorganic nanoparticles. The modification strategy can realize that two or more than two different polymer ligands are modified on the surfaces of the inorganic nanoparticles according to the specified grafting ratio. The method comprises the following steps: a) synthesizing an initiator with a structure capable of realizing interconnection, wherein the initiator contains at least one initiating group and at least two groups capable of reacting with each other; b) preparing different types of polymers with different molecular weights through atom transfer radical polymerization; c) mutually connecting polymers with different types and different molecular weights according to a designed proportion by utilizing sites capable of mutually reacting on the initiator; and d) modifying the prepared multi-component distribution body on the surface of the nano particle through a ligand exchange method or a chemical reaction. The modification strategy provided by the invention is suitable for nanoparticles with different sizes and different materials and polymer ligands with different types and different molecular weights. The obtained multi-ligand modified nano particles can realize different functionalization according to the physicochemical properties of the surface polymer, and can be used as functionalized nano composite materials, such as an emulsion fixing stabilizer, a hydrophilic-hydrophobic conversion material, a catalyst, a drug targeting hydrophobic material, an optical biosensor and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of polymer / inorganic nanocomposite materials, and more specifically, relates to a modification strategy for controlling the proportion of multiple ligand grafting on the surface of inorganic nanoparticles. Background Art

[0002] Due to the natural properties and unique effects of inorganic nanoscale (such as small size effect, Kubo effect and quantum confinement effect), it shows great application potential in photovoltaic materials, microelectronic devices, high-sensitivity sensors, etc. In addition, through the coordination between inorganic nanoparticles and specific groups, polymer ligands can be modified on the surface to give nanoparticles additional functions and responsiveness. And by using the interaction between polymer ligands, nanoparticles can be driven to assemble into an ordered hierarchical structure, and its performance can be further enhanced compared with single nanoparticles.

[0003] At present, there are two main strategies for introducing ligands onto nanoparticles: "graft from" and "graft to". In the "graft from" method, reactive molecules or initiators are first grafted onto the surface of inorganic nanoparticles, and then the specified polymer ligands are further synthesized on the surface. In contrast, in the "graft to" method, the synthesized polymer ligands are directly grafted onto the surface of inorganic nanoparticles. However, in both methods, the uncontrollable number of binding sites leads to uncertain grafting density. This disadvantage is particularly evident when inorganic nanoparticles are modified with two or more polymer ligands. This results in huge differences in grafting density between different types of polymers, which greatly affects the accurate expression of the functionality of multi-ligand modified inorganic nanoparticles.

[0004] To address this problem, designing and synthesizing reactive molecules or initiators with special structures is a feasible strategy. Among them, Y-type initiators have been reported more frequently. The initiator contains two arms with different specific groups, which respectively initiate different types of controlled active polymerization (such as ATRP, RAFT or NMRP) to obtain block polymers, and the middle arm contains specific groups (such as thiol, amino, etc.) grafted to the surface of inorganic nanoparticles. Therefore, a double ligand with a grafting density ratio of 1:1 can be obtained. However, this type has several important defects. 1) It is only applicable to multi-ligand modification systems with relatively simple grafting density ratios such as 1:1 and 1:2, and the designability is not strong; 2) The synthesis steps are complicated, especially for complex multi-arm initiators; 3) The step-by-step polymerization method means that the steric hindrance generated by the first polymer synthesized will affect the subsequent polymerization, resulting in a wider final molecular weight distribution; 4) For different multi-ligand systems, the polymerization needs to be restarted, which is cumbersome and time-consuming. Therefore, how to develop a new multi-ligand modification strategy with designability and controllable grafting ratio is still a huge challenge. Summary of the invention

[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles. An initiator with a special structure is designed and synthesized, which contains at least one initiating group A that can initiate atom transfer radical polymerization (ATRP) and at least two groups B and C that can react with each other, wherein the group B needs to be protected to reduce its reactivity. Compared with the Y-type initiator, this initiator has multiple advantages: 1) The initiator only undergoes polymerization once, so it is not affected by steric hindrance and can obtain a polymer ligand product with a narrow molecular weight distribution; 2) Groups B and C can form covalent bonds through chemical reactions. By utilizing this, the connection between polymer ligands of different types and molecular weights can be achieved; 3) Group B first adopts a protection strategy to reduce its reactivity, which does not affect the polymerization reaction. At the same time, the obtained polymer can be stored for a long time without intermolecular or intramolecular interactions, and has good stability. Its reactivity can be restored by a simple deprotection reaction before use; 4) In the early stage, this initiator can be used to prepare a large number of polymers of different types and molecular weights as "elements". When needed, different "elements" can be selected and matched according to design requirements and proportions, without the need to re-polymerize. It is not only highly designable, but also simplifies the steps and shortens the process; 5) After different types of polymers are overlapped with each other, they are connected to inorganic nanoparticles through the same reaction site, ensuring the grafting ratio between different types of polymers. This strategy provides a simple way to modify the surface of inorganic nanoparticles with controllable multi-ligand grafting ratios, which helps to achieve precise control of multiple functional ligands on the surface of inorganic nanoparticles, thereby enhancing the application of nanoparticles in photovoltaic materials, microelectronic devices and high-sensitivity sensors.

[0006] To achieve the above object, according to one aspect of the present invention, a technical method for preparing an initiator that can be connected to polymer multi-ligand modified nanoparticles is provided, comprising the following steps:

[0007] (1) Preparation of initiators: Design and synthesize an initiator with a specified structure. The initiator structure must contain at least one initiating group A that can initiate atom transfer radical polymerization (ATRP) and at least two groups B and C that can react with each other. Group B must first be protected to reduce its reactivity.

[0008] (2) Preparation of polymers: Using the initiator of step (1), polymers of different types and molecular weights are synthesized by ATRP polymerization.

[0009] (3) Linking polymers: Select one of the polymers synthesized in step (2), modify the group C at its end, and convert it into a group D that can react with the functional groups or atoms on the surface of the nanoparticles. Then deprotect the protected group B to restore its reactivity. Select another polymer, and use the interaction between its terminal group C and the terminal group B of the first polymer to achieve the connection of the two polymers. This process can be repeated multiple times according to the target grafting ratio.

[0010] (4) Polymer-modified nanoparticles: The ligands obtained by linking multiple polymers obtained in step (3) are dissolved in a solvent and modified onto the surface of inorganic nanoparticles by ligand exchange or chemical reaction.

[0011] Preferably, the initiating group A in step (1) is one of bromine and chlorine; the group B is one of amino (-NH2) and hydroxyl (-OH); and the group C is carboxyl (-COOH).

[0012] Preferably, the protection strategy described in step (1), when group B is an amino group, is one of tert-butyloxycarbonyl protection, benzyloxycarbonyl protection, fluorenylmethyloxycarbonyl protection, and trityl protection; when group B is a hydroxyl group, is one of etherification protection, esterification protection, ketal protection, or acetal protection.

[0013] Preferably, the polymerization method in step (2) is applicable to any monomer containing an unsaturated double bond.

[0014] Preferably, the group D in step (3) is one of a thiol group, a carboxyl group, an amino group, a siloxane group, and a disulfide bond.

[0015] Preferably, the deprotection treatment strategy of the group A in step (3) is one of acidic deprotection, catalytic hydrogenation deprotection and alkaline deprotection.

[0016] Preferably, the grafting ratio in step (3) can be designed at any ratio as required.

[0017] Preferably, the nanoparticles in step (4) include gold nanoparticles, silver nanoparticles, ferroferric oxide nanoparticles, silicon dioxide nanoparticles, and quantum dots such as cadmium selenide, zinc sulfide, and lead halide cesium perovskite.

[0018] According to another aspect of the present invention, a multi-ligand modified nanoparticle is provided, characterized in that the nanoparticle comprises gold nanoparticles, silver nanoparticles, ferroferric oxide nanoparticles, silicon dioxide nanoparticles and one of quantum dots such as cadmium selenide, zinc sulfide, and lead halide cesium perovskite; the surface ligand is two or more polymers, and the grafting ratio thereof can be controlled according to design requirements.

[0019] According to another aspect of the present invention, a multi-ligand modified nanoparticle is provided, characterized in that it can be used as an emulsion fixation stabilizer, a hydrophilic-hydrophobic conversion material, a solid-phase catalyst, a drug targeting material, an optical biosensor, etc.

[0020] In general, compared with the prior art, the above technical solution conceived by the present invention can achieve the following beneficial effects.

[0021] 1) The present invention provides a modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles. First, an initiator with a special structure is designed and synthesized, which contains at least one initiating group A that can initiate atom transfer radical polymerization (ATRP) and at least two groups B and C that can react with each other, wherein the group B needs to be protected to reduce its reactivity; the initiator is used to carry out polymerization to obtain polymers of different types and molecular weights; a polymer is selected, and its group C is converted into a group D that can coordinate with the surface of inorganic nanoparticles; the protection of group B is removed to restore its reactivity, and then the interaction between group B and group C of another polymer is used to connect different polymers together, and this process can be repeated according to the target design ratio; the ligands obtained by connecting multiple polymers are dissolved in a solvent, and modified to the surface of inorganic nanoparticles by ligand exchange or chemical reaction.

[0022] 2) In this method, since the designed and synthesized initiator only needs to undergo one polymerization reaction, it is not affected by steric hindrance and can obtain a polymer ligand product with a narrow molecular weight distribution.

[0023] 3) Groups B and C can form covalent bonds through chemical reactions, and this can be used to achieve the connection between polymer ligands of different types and molecular weights.

[0024] 4) A protection strategy is first adopted for group B to reduce its reactivity, that is, it does not affect the polymerization reaction. At the same time, the obtained polymer can be stored for a long time without any intermolecular or intramolecular interaction, and has good stability. Its reactivity can be restored by a simple deprotection reaction before use.

[0025] 5) In the early stage, the initiator can be used to prepare a large number of polymers of different types and molecular weights as "components". When needed, different "components" can be selected and matched according to design requirements and proportions, without the need to re-polymerize. It not only has strong designability, but also simplifies steps and shortens the process.

[0026] 6) After different types of polymers are overlapped with each other, they are connected to inorganic nanoparticles through the same reaction site, thus ensuring the grafting ratio between different types of polymers.

[0027] 7) The present invention provides a modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, which can be used for any monomer containing unsaturated double bonds and can be adapted to the surface modification of various inorganic nanoparticles. It is simple to operate, takes less time, and has strong repeatability.

[0028] 8) The present invention provides a modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, which can be designed and realized according to actual needs, so that polymer ligands of different types and molecular weights can be connected in a specified ratio. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of a process for a modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles according to the present invention;

[0030] Figure 2 The chemical structural formula and infrared spectrum of the initiator designed in Example 1;

[0031] Figure 3 is a data table of molecular weight and molecular weight distribution of the polymer product obtained by polymerization initiated by the initiator designed in Example 1;

[0032] Figure 4 This is a transmission electron microscope image of a multi-ligand modified nanoparticle finally obtained in Example 1. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0034] The present invention provides a modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, comprising the following steps:

[0035] (1) Preparation of initiators: Design and synthesize an initiator with a specified structure. The initiator structure must contain at least one initiating group A that can initiate atom transfer radical polymerization (ATRP) and at least two groups B and C that can react with each other. Group B must first be protected to reduce its reactivity.

[0036] Among them, the initiating group A is one of bromine and chlorine; the group B is one of amino (-NH2) and hydroxyl (-OH), and the group C is carboxyl (-COOH); the protection strategy, when the group B is amino, is one of tert-butyloxycarbonyl protection, benzyloxycarbonyl protection, fluorenylmethyloxycarbonyl protection, and trityl protection; when the group B is hydroxyl, the strategy is one of etherification protection, esterification protection, ketal or acetal protection.

[0037] (2) Preparation of polymers: Using the initiator of step (1), polymers of different types and molecular weights are synthesized by ATRP polymerization.

[0038] The polymerization method is applicable to any monomer containing an unsaturated double bond.

[0039] (3) Linking polymers: Select one of the polymers synthesized in step (2), modify the group C at its end, and convert it into a group D that can react with the functional groups or atoms on the surface of the nanoparticles. Then deprotect the protected group B to restore its reactivity. Select another polymer, and use the interaction between its terminal group C and the terminal group B of the first polymer to achieve the connection of the two polymers. This process can be repeated multiple times according to the target grafting ratio.

[0040] Wherein, the group D is one of thiol, carboxyl, amino, siloxane group, and disulfide bond; the deprotection treatment strategy of the group A is one of acidic deprotection, catalytic hydrogenation deprotection, and alkaline deprotection; the grafting ratio can be designed according to any ratio as needed.

[0041] (4) Polymer-modified nanoparticles: The ligands obtained by linking multiple polymers obtained in step (3) are dissolved in a solvent and modified onto the surface of inorganic nanoparticles by ligand exchange or chemical reaction.

[0042] The nanoparticles include gold nanoparticles, silver nanoparticles, ferroferric oxide nanoparticles, silicon dioxide nanoparticles, and quantum dots such as cadmium selenide, zinc sulfide, and lead halide cesium perovskite.

[0043] The multi-ligand modified nanoparticles provided by the present invention include nanoparticles and multiple ligand polymers, and the polymers are grafted on the surface of the nanoparticles. The nanoparticles include gold nanoparticles, silver nanoparticles, ferroferric oxide nanoparticles, silicon dioxide nanoparticles, and quantum dots such as cadmium selenide, zinc sulfide, and lead halide cesium perovskite; the surface ligands are two or more polymers, and the grafting ratio can be controlled according to design requirements. The multi-ligand modified nanoparticles can be used for emulsion fixation stabilizers, hydrophilic-hydrophobic conversion materials, solid-phase catalysts, drug targeting materials, and optical biosensors.

[0044] The present invention can realize the controllable modification of the grafting ratio of multiple ligands on the surface of inorganic nanoparticles. The key point lies in the special structure initiator designed and synthesized in step (1), which contains at least one initiating group A that can initiate atom transfer radical polymerization (ATRP) and at least two groups B and C that can react with each other, wherein the group B needs to be protected to reduce its reactivity. The initiating group A in the initiator can be used to initiate polymerization to obtain polymers of different types and different molecular weights; and by deprotecting the group B, its reactivity can be restored. The chemical reaction of the groups B and C on different types of polymer ligands can be used to connect them with each other. This process can select polymers of any type and molecular weight to connect in any proportion according to actual needs. Finally, the overlapped multi-ligand polymer is modified on the surface of the nanoparticle to realize the controllable modification of the ratio of multiple ligands on the surface of the nanoparticle.

[0045] According to this method, the controllable modification of the grafting ratio of multiple ligands on the surface of inorganic nanoparticles can be successfully achieved. Any monomer containing unsaturated double bonds can be adapted to the surface modification of various inorganic nanoparticles. The operation is simple, time-saving and highly repeatable. According to actual needs, different types and molecular weight polymer ligands can be designed and connected in a specified ratio.

[0046] The following are examples:

[0047] Example 1

[0048] A modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, the specific steps are as follows

[0049] 1) Preparation of initiator: L-lysine is used as a skeleton compound, which contains two amino groups and one carboxyl group, wherein the amino group and the carboxyl group can react with each other. First, the ε-amino group is protected by benzyloxycarbonyl (Cbz), and then bromoisobutyryl bromide is used to react with the α-amino group to introduce bromine at the initiation site to obtain an initiator of a specified structure. It contains an initiating group A (bromine) that initiates atom transfer free radical polymerization, and groups B (amino group) and C (carboxyl group) that can react with each other, wherein the amino group is protected by Cbz.

[0050] (2) Preparation of polymer: using the initiator of step (1) to synthesize polystyrene and polymethyl methacrylate of different molecular weights by ATRP polymerization.

[0051] (3) Linking between polymers: Select step (2) to synthesize polystyrene (molecular weight 10,000 g / mol), modify its terminal carboxyl group, and convert it into a thiol group that can react with the surface of gold nanoparticles. Then, the Cbz-protected amino group is catalytically hydrogenated to achieve deprotection and restore its reaction activity. Then select polymethyl methacrylate (molecular weight 18,000 g / mol), and use the amidation between its terminal carboxyl group and the terminal amino group of polystyrene to achieve the connection between the two polymers. A multi-ligand polymer with a grafting ratio of 1:1 is obtained.

[0052] (4) Polymer-modified nanoparticles: The multi-ligand polymer with a grafting ratio of 1:1 obtained in step (3) is dissolved in chloroform and modified onto the surface of gold nanoparticles by a ligand exchange method.

[0053] Example 2

[0054] A modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, the specific steps are as follows

[0055] 1) Preparation of initiator: Serine is used as a skeleton compound, which contains an amino group, a carboxyl group and a hydroxyl group, wherein both the amino group and the hydroxyl group can react with the carboxyl group. First, the hydroxyl group is protected by etherification, and then bromoisobutyryl bromide is used to react with the amino group to introduce bromine at the initiation site to obtain an initiator of a specified structure. It contains an initiating group A (bromine) for initiating atom transfer free radical polymerization, and groups B (hydroxyl group) and C (carboxyl group) that can react with each other, wherein the amino group is protected by etherification.

[0056] (2) Preparation of polymers: using the initiator of step (1) to synthesize polystyrene, polyacrylamide and polyisopropylacrylamide of different molecular weights by ATRP polymerization.

[0057] (3) Linking between polymers: Select step (2) to synthesize polystyrene (molecular weight 5,000 g / mol), modify its terminal carboxyl group, and convert it into a siloxane group that can react with the surface of silica nanoparticles. Then, deprotect the etherified hydroxyl group in an acidic environment to restore its reactivity. Then select polyacrylamide (molecular weight 10,000 g / mol), and use the esterification reaction between its terminal carboxyl group and the terminal hydroxyl group of polystyrene to achieve the connection between the two polymers; then deprotect the etherified hydroxyl group at the end of polyacrylamide in an acidic environment to restore its reactivity. Select polyisopropylacrylamide (molecular weight 15,000 g / mol), and use the esterification reaction between its terminal carboxyl group and the terminal hydroxyl group of polyacrylamide to connect the third polymer to obtain a multi-ligand polymer with a grafting ratio of 1:1:1.

[0058] (4) Polymer-modified nanoparticles: The multi-ligand polymer with a grafting ratio of 1:1:1 obtained in step (3) is dissolved in N,N-dimethylformamide and modified onto the surface of silica nanoparticles through the interaction between siloxane groups and silanol groups.

[0059] Example 3

[0060] A modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, the specific steps are as follows

[0061] 1) Preparation of initiator: L-glutamic acid is used as a skeleton compound, which contains one amino group and two carboxyl groups, wherein the amino group and the carboxyl group can react with each other. First, the amino group is protected by tert-butyloxycarbonyl (Boc), and then 2-bromoethylamine hydrobromide is used to react with one carboxyl group to introduce bromine at the initiation site to obtain an initiator of a specified structure. It contains an initiating group A (bromine) for initiating atom transfer free radical polymerization, and groups B (hydroxyl) and C (carboxyl) that can react with each other, wherein the amino group is protected by Boc.

[0062] (2) Preparation of polymer: using the initiator of step (1) to synthesize polypropylene and polybutadiene of different molecular weights by ATRP polymerization.

[0063] (3) Linking between polymers: Select step (2) to synthesize polypropylene (molecular weight 20,000 g / mol), modify its terminal carboxyl group, and convert it into an amino group that can react with the surface of silver nanoparticles. Then, the Boc-protected amino group is deprotected in an acidic environment to restore its reactivity. Then, polybutadiene (molecular weight 50,000 g / mol) is selected, and the amidation reaction between its terminal carboxyl group and the terminal amino group of polypropylene is used to connect the two polymers; then, the Boc-protected amino group at the end of polybutadiene is deprotected in an acidic environment to restore its reactivity. Polybutadiene (molecular weight 50,000 g / mol) is used again, and the second polybutadiene is connected to it by the amidation reaction between its terminal carboxyl group and the terminal amino group of the first polybutadiene, thereby obtaining a multi-ligand polymer with a grafting ratio of 1:2.

[0064] (4) Polymer-modified nanoparticles: The multi-ligand polymer with a grafting ratio of 1:2 obtained in step (3) is dissolved in tetrahydrofuran, and modified onto the surface of silver nanoparticles through the interaction between the amino group and silver.

[0065] Example 4

[0066] A modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, the specific steps are as follows

[0067] 1) Preparation of initiator: Threonine is used as a skeleton compound, which contains an amino group, a carboxyl group and a hydroxyl group, wherein the amino group and the hydroxyl group can react with the carboxyl group. First, the hydroxyl group is protected by esterification, and then bromoisobutyryl bromide is used to react with the amino group to introduce bromine at the initiation site to obtain an initiator of a specified structure. It contains an initiating group A (bromine) for initiating atom transfer free radical polymerization, and groups B (hydroxyl group) and C (carboxyl group) that can react with each other, wherein the amino group is protected by etherification.

[0068] (2) Preparation of polymer: Poly(4-vinylpyridine) and polyvinyl chloride of different molecular weights were synthesized by ATRP polymerization using the initiator of step (1).

[0069] (3) Linking between polymers: Select step (2) to synthesize poly(4-vinylpyridine) (molecular weight of 5,000 g / mol). Since the carboxyl group can react with the surface of the ferroferric oxide nanoparticles, the terminal carboxyl group is not modified and is retained. The esterified hydroxyl group is then deprotected in an alkaline environment to restore its reactivity. Then, polyvinyl chloride (molecular weight, 5,000 g / mol) is selected, and the two polymers are connected by the reaction between its terminal carboxyl group and the terminal hydroxyl group of poly(4-vinylpyridine); the esterified hydroxyl group of the polyvinyl chloride is then deprotected in an acidic environment to restore its reactivity. Polyvinyl chloride (molecular weight of 5,000 g / mol) is used again, and the second polyvinyl chloride is connected by the reaction between its terminal carboxyl group and the terminal hydroxyl group of the first polyvinyl chloride; the esterified hydroxyl group of the second polyvinyl chloride is then deprotected in an acidic environment to restore its reactivity. Polyvinyl chloride (molecular weight of 5,000 g / mol) was used again, and the third polyvinyl chloride was connected to it by utilizing the reaction between its terminal carboxyl group and the terminal hydroxyl group of the second polyvinyl chloride; a multi-ligand polymer with a grafting ratio of 1:3 was obtained.

[0070] (4) Polymer modified nanoparticles: The multi-ligand polymer with a grafting ratio of 1:3 obtained in step (3) is dissolved in toluene, and modified onto the surface of the ferrosoferric oxide nanoparticles through the interaction between the carboxyl group and ferrosoferric oxide.

[0071] Example 5

[0072] A modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, the specific steps are as follows

[0073] 1) Preparation of initiator: L-lysine is used as a skeleton compound, which contains two amino groups and one carboxyl group, wherein the amino group and the carboxyl group can react with each other. First, the ε-amino group is protected by fluorenylmethoxycarbonyl (Fmoc), and then bromoisobutyryl bromide is used to react with the α-amino group to introduce bromine at the initiation site to obtain an initiator of a specified structure. It contains an initiating group A (bromine) that initiates atom transfer free radical polymerization, and groups B (amino group) and C (carboxyl group) that can react with each other, wherein the amino group is protected by Cbz.

[0074] (2) Preparation of polymers: using the initiator of step (1) to synthesize polybutene and polystyrene of different molecular weights by ATRP polymerization.

[0075] (3) Linking polymers: Select step (2) to synthesize polybutene (molecular weight 20,000 g / mol), modify its terminal carboxyl group, and convert it into a dithiol bond that can react with the surface of gold nanoparticles. Then, the Fmoc-protected amino group is treated with acid to achieve deprotection and restore its reactivity. Then select polystyrene (molecular weight 10,000 g / mol), and use the amidation between its terminal carboxyl group and the terminal amino group of polybutene to achieve the connection between the two polymers. A multi-ligand polymer with a grafting ratio of 1:1 is obtained.

[0076] (4) Polymer-modified nanoparticles: The multi-ligand polymer with a grafting ratio of 1:1 obtained in step (3) is dissolved in chloroform and modified onto the surface of gold nanoparticles by a ligand exchange method.

[0077] Example 6

[0078] A modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, the specific steps are as follows

[0079] 1) Preparation of initiator: Serine is used as a skeleton compound, which contains an amino group, a carboxyl group and a hydroxyl group, wherein both the amino group and the hydroxyl group can react with the carboxyl group. First, the hydroxyl group is protected by ketalization, and then bromine is introduced into the initiation site by reacting with the amino group using bromoisobutyryl bromide to obtain an initiator with a specified structure. It contains an initiating group A (bromine) for initiating atom transfer free radical polymerization, and groups B (hydroxyl group) and C (carboxyl group) that can react with each other, wherein the amino group is protected by etherification.

[0080] (2) Preparation of polymer: using the initiator of step (1) to synthesize polystyrene and polymethyl methacrylate of different molecular weights by ATRP polymerization.

[0081] (3) Linking between polymers: Select step (2) to synthesize polystyrene (molecular weight of 15,000 g / mol). Since the carboxyl group can react with the surface of cadmium selenide quantum dots to coordinate, the terminal carboxyl group is not modified here and is retained. The hydroxyl group protected by the ketal is then deprotected in an acidic environment to restore its reactivity. Select polystyrene (molecular weight of 15,000 g / mol) again, and use the esterification reaction between its terminal carboxyl group and the terminal hydroxyl group of the first polystyrene to achieve connection; then deprotect the hydroxyl group protected by the ketal at the end of the second polystyrene in an acidic environment to restore its reactivity; then select polymethyl methacrylate (molecular weight of 20,000 g / mol) and use the esterification reaction between its terminal carboxyl group and the terminal hydroxyl group of polystyrene to achieve connection; obtain a multi-ligand polymer with a grafting ratio of 2:1.

[0082] (4) Polymer-modified nanoparticles: The multi-ligand polymer with a grafting ratio of 2:1 obtained in step (3) is dissolved in dichloromethane, and modified onto the surface of cadmium selenide quantum dots through the interaction between carboxyl groups and cadmium atoms.

[0083] Example 7

[0084] A modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, the specific steps are as follows

[0085] 1) Preparation of initiator: L-glutamic acid is used as a skeleton compound, which contains an amino group and two carboxyl groups, wherein the amino group and the carboxyl group can react with each other. First, the amino group is protected by trityl protection, and then 2-bromoethylamine hydrobromide is used to react with a carboxyl group to introduce bromine at the initiation site to obtain an initiator of a specified structure. It contains an initiating group A (bromine) for initiating atom transfer free radical polymerization, and groups B (hydroxyl) and C (carboxyl) that can react with each other, wherein the amino group is protected by Boc.

[0086] (2) Preparation of polymers: using the initiator of step (1) to synthesize polyvinyl chloride, polyisobutylene and polyvinyl acetate of different molecular weights by ATRP polymerization.

[0087] (3) Linking between polymers: Select step (2) to synthesize polyvinyl chloride (molecular weight 50,000 g / mol). Since the carboxyl group can coordinate with the surface of zinc sulfide quantum dots, the terminal carboxyl group is not modified here and is retained. The amino group protected by trityl is then deprotected in an acidic environment to restore its reactivity. Then, polyisobutylene (molecular weight 100,000 g / mol) is selected, and the amidation reaction between its terminal carboxyl group and the terminal amino group of polyvinyl chloride is used to connect the two polymers; then, the amino group protected by trityl at the end of polyisobutylene is deprotected in an acidic environment to restore its reactivity. Then, polyvinyl acetate (molecular weight, 50,000 g / mol) is used, and the amidation reaction between its terminal carboxyl group and the terminal amino group of polyisobutylene is used to connect polyvinyl acetate to obtain a multi-ligand polymer with a grafting ratio of 1:1:1.

[0088] (4) Polymer-modified nanoparticles: The multi-ligand polymer with a grafting ratio of 1:1:1 obtained in step (3) is dissolved in tetrahydrofuran, and modified onto the surface of zinc sulfide quantum dots through the interaction between the carboxyl group and zinc.

[0089] Example 8

[0090] A modification strategy for controlling the ratio of multiple ligand grafting on the surface of inorganic nanoparticles, the specific steps are as follows

[0091] 1) Preparation of initiator: Threonine is used as a skeleton compound, which contains an amino group, a carboxyl group and a hydroxyl group, wherein the amino group and the hydroxyl group can react with the carboxyl group. First, the hydroxyl group is protected by acetalization, and then bromoisobutyryl bromide is used to react with the amino group to introduce bromine at the initiation site to obtain an initiator of a specified structure. It contains an initiating group A (bromine) for initiating atom transfer free radical polymerization, and groups B (hydroxyl group) and C (carboxyl group) that can react with each other, wherein the amino group is protected by etherification.

[0092] (2) Preparation of polymer: using the initiator of step (1) to synthesize polychloroprene and polystyrene of different molecular weights by ATRP polymerization.

[0093] (3) Linking between polymers: Select step (2) to synthesize polychloroprene (molecular weight 15,000 g / mol). Since the carboxyl group can react with the surface of lead halide cesium perovskite quantum dots, the terminal carboxyl group is not modified and is retained. The acetal-protected hydroxyl group is then deprotected in an alkaline environment to restore its reactivity. Polystyrene (molecular weight 5,000 g / mol) is then selected, and the reaction between its terminal carboxyl group and the terminal hydroxyl group of polychloroprene is used to achieve the connection between the two polymers, thereby obtaining a multi-ligand polymer with a grafting ratio of 1:1.

[0094] (4) Polymer-modified nanoparticles: The multi-ligand polymer with a grafting ratio of 1:1 obtained in step (3) is dissolved in hexane, and modified onto the surface of the lead halide cesium perovskite quantum dots through the interaction between the carboxyl groups and the lead ions.

Claims

1. A modification strategy for inorganic nanoparticle surfaces with controllable grafting ratios of multiple ligands, which can achieve modification of the inorganic nanoparticle surfaces with two or more different polymer ligands at a specified grafting ratio, characterized in that: The steps include: (1) Preparation of initiators: Design and synthesize an initiator with a specified structure. The initiator structure must contain at least one initiating group A that can initiate atom transfer radical polymerization (ATRP) and at least two groups B and C that can react with each other. Group B must first be protected to reduce its reactivity. (2) Preparation of polymers: Using the initiator of step (1), polymers of different types and molecular weights are synthesized by ATRP polymerization. (3) Linking polymers: Select one of the polymers synthesized in step (2), modify the group C at its end, and convert it into a group D that can react with the functional groups or atoms on the surface of the nanoparticles. Then deprotect the protected group B to restore its reactivity. Select another polymer, and use the interaction between its terminal group C and the terminal group B of the first polymer to achieve the connection of the two polymers. This process can be repeated multiple times according to the target grafting ratio. (4) Polymer-modified nanoparticles: The ligands obtained by linking multiple polymers obtained in step (3) are dissolved in a solvent and modified onto the surface of inorganic nanoparticles by ligand exchange or chemical reaction.

2. The modification strategy according to claim 1, characterized in that In step (1), the initiating group A is one of bromine and chlorine; the group B is one of amino (-NH2) and hydroxyl (-OH); and the group C is carboxyl (-COOH).

3. The modification strategy according to claim 1, characterized in that The protection strategy described in step (1) is one of tert-butyloxycarbonyl protection, benzyloxycarbonyl protection, fluorenylmethyloxycarbonyl protection, and trityl protection when group B is an amino group, and one of etherification protection, esterification protection, ketal protection, or acetal protection when group B is a hydroxyl group.

4. The preparation method according to claim 1, characterized in that: The polymerization method described in step (2) is applicable to any monomer containing an unsaturated double bond.

5. The preparation method according to claim 1, characterized in that: The group D in step (3) is one of a thiol group, a carboxyl group, an amino group, a siloxane group, and a disulfide bond.

6. The preparation method according to claim 1, characterized in that: The deprotection treatment strategy of the group A in step (3) is one of deprotection under acidic conditions, catalytic hydrogenation deprotection, and deprotection under alkaline conditions.

7. The preparation method according to claim 1, characterized in that: The grafting ratio in step (3) can be designed at any ratio as required.

8. The preparation method according to claim 1, characterized in that: The nanoparticles in step (4) include gold nanoparticles, silver nanoparticles, ferroferric oxide nanoparticles, silicon dioxide nanoparticles, and quantum dots such as cadmium selenide, zinc sulfide, and lead halide cesium perovskite.

9. A multi-ligand modified nanoparticle prepared according to the preparation method of claim 1, characterized in that: The nanoparticles include gold nanoparticles, silver nanoparticles, ferroferric oxide nanoparticles, silicon dioxide nanoparticles and quantum dots such as cadmium selenide, zinc sulfide, and lead halide cesium perovskite; the surface ligands are two or more polymers, and the grafting ratio can be controlled according to design requirements.

10. A multi-ligand modified nanoparticle prepared according to the preparation method of claim 1, characterized in that: It can be used as emulsion fixation stabilizer, hydrophilic-hydrophobic conversion material, solid-phase catalyst, drug targeting material and optical biosensor, etc.

Citation Information

Patent Citations

  • Nano particle surface modifying method

    CN101177470A

  • Dual-ligand Janus nano-particle as well as preparation method and application thereof

    CN109776843A

  • Atom transfer radical polymerization (ATRP) based inorganic polymer structures

    US20100227162A1